Labour market power and the quest for an optimal minimum wage: evidence from Italy. Issue 15 (28th March 2023) - Caselli, Mauro; Mondolo, Jasmine; Schiavo, Stefano
ABSTRACT: This study investigates the recent trends in labour market power in Italy and assesses the impact of a potential minimum wage using a large sample of manufacturing firms. We show that, despite an average shift of labour market power from companies to workers, monopsony power is still widespread, especially in some sectors and regions. The introduction of a minimum wage would be beneficial to workers and the economy as it reduces the monopsony power of highly productive firms paying low wages; however, it may also have a negative impact, since firms with low wages and low labour productivity may react by reducing the number of their employees or even by exiting the market. Finally, we find that an optimal minimum wage, which minimizes the negative effect and maximizes the positive effect for the economy, ranges between 8.25 and 9.65 euro per hour.